EXAMINATION OF EFFECTS OF ARTHYSRIC GYMNASTICS TEACHING OF PHYSICAL EDUCATION ON FUNCTIONALL ABYLITIES OF 3RD & 4TH GRADE PUPILS OF ELEMENTARY SCHOOLS - Dragana Aleksić; Branimir Mekić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
In this work, the subject of the research is only one segment of the anthropological area, which refers to the appearance of appropriate morphological characteristic. The research involved a total sample of 107 girls from the 3th and 4th grade of elementary school. The subjects were classified in experimental and control groups. The experimental group was made of 59 students and they were practicing according to planning instruction where the arthystic gymnastics had the primary part. The control group of 48 students was practicing according to official instructional plan and program for P.E. of the Republic of Serbia. The battery for the evaluation of functional abilities consists of the following tests: vital capacity by spirometer, Lorenc`s test and heart puls in peace. Research data was processed using SPSS standard statistics procedure. There were calculated: Basic statistics parameters (mean, standard deviation, Min/Max numeric score, interval of confidence, coefficient of variation), Descriptive statistic parameters, Kolmogorov-Smirnov test for the evaluation of normality of test result distribution of applied variables. The multi-variant procedures were used in this research ant those were: the multi-variant analysis of the variable (MANOVA) and the discriminative analysis. Also, the mono-variant procedures were used and those were: the variable analysis (ANOVA) and the interval of entrust. After the experimental treatment, i.e. at the final testing, significant differences were found with female pupils in experimental and control groups concerning the two of four tests for the evaluation of functional abilities.